Witches and Demons: The Occult in Two Hammer Films from the 1960s - Michael Wood (Monstrum, 2018)
Discusses the parallels and shared context regarding two of Hammer Studios' 1960s occult films, The Devil Rides Out and The Witches, the latter largely forgotten.